THE ROLE OF STUDENT SELF-GOVERNMENT IN THE SELF-FULFILLMENT OF STUDENTS OF THE INSTITUTION OF HIGHER EDUCATION - Бялик, Оксана (Modern engineering and innovative technologies, 2022)
The article analyzes the role of student self-government in the self-realization of students of a higher education institution, which consists in revealing all aspects of an individual’s life, providing opportunities to develop abilities, implement life p